Exposure in vivo Induced Changes in Neural Circuitry for Pain-Related Fear: A Longitudinal fMRI Study in Chronic Low Back Pain - Timmers, Inge; de Jong, Jeroen R.; Goossens, Mariëlle; Verbunt, Jeanine A.; Smeets, Rob J.; Kaas, Amanda L. (Frontiers in Neuroscience, 2019)
Exposure in Vivo (EXP) is a cognitive-behavioral treatment aimed at reducing pain-related fear in chronic pain, and has proven successful in reducing pain-related disability in patients with chronic low back pain (cLBP). The current longitudinal study aimed to reveal the neural correlates of changes in pain-related fear as a result of EXP. Twenty-three patients with cLBP were included in this study. Patients with cLBP underwent MRI scanning pre-treatment (pre-EXP), post-treatment (post-EXP), and six months after end of treatment (FU-EXP). Pain-free controls were scanned at two time points. In the scanner, participants were presented with pictures involving back-related movements, evoking pain-related fear in patients. Pre-treatment, functional MRI revealed increased activation in right posterior insula and increased deactivation in medial prefrontal cortex (mPFC) in patients compared to controls. Post-treatment, patients reported reduced fear and pre-EXP group differences were no longer present. Contrasting pre- to post- and FU-EXP in patients revealed that stimulus-evoked neural responses changed in sensorimotor as well as cognitive/affective brain regions. Lastly, exploratory analyses revealed a tendency towards an association between changes in neural activation and changes in fear ratings, including the hippocampus and temporal lobe (pre- to post-EXP changes), and mPFC and posterior cingulate cortex (pre- to FU-EXP changes). Taken together, we show evidence that neural circuitry for pain-related fear is modulated by EXP, and that changes are associated with self-reported decreases in pain-related fear.